Strategic Responses on Population Ageing in Regional Policy - Andrzej Klimczuk (Theory of Management, 4. The Selected Problems for the Development Support of Management Knowledge Base, 2011)
Population ageing is one of the key processes affecting the development of European Union countries. The aim of this paper is an indication of the possibility of collective action against this challenge at the regional level. Article describe assumptions and recommendations for strategic management which taking into account the cooperation of entities from public sector (local governments), market sector (business) and social sector (NGOs). Closer analyses will be conducted on two examples of initiatives from European Union: the Regions for All Ages programme and network organization SEN@ER - Silver Economy Network of European Regions. The summary will indicate possible directions of further research.
Keywords: J14; P25; Z18; 330; regional and local development; strategic management; cross-sector cooperation; silver economy; Strategic Management; Urban Economics